Integrating ultrashort-chain compounds into the comprehensive analysis of per- and polyfluorinated substances in ready-to-feed liquid milk samples - Shun-Hsin Liang; Justin A. Steimling (Journal of Chromatography Open)
Ultrashort-chain (USC) per- and polyfluoroalkyl substances (PFAS) are highly polar compounds with carbon chains shorter than C4. Their widespread occurrence in aquatic environments has raised growing concerns about potential contamination in food products, particularly ready-to-feed liquid milk. To fully assess and mitigate PFAS contamination, it is essential to include USC compounds in PFAS analysis of milk samples. The high polarity of USC PFAS poses a significant challenge for standard chromatographic practices in PFAS analysis, primarily due to insufficient chromatographic retention. This study introduces a simple and reliable workflow for the simultaneous analysis of C1 to C14 perfluoroalkyl carboxylic and sulfonic acids, along with other PFAS classes, in various liquid milk matrices. The chromatographic analysis was performed using an inert-coated polar-embedded alkyl phase LC column. Method verification was conducted using three different milk types—dairy milk, almond milk, and infant formula—to demonstrate the workflow’s applicability for measuring 41 PFAS in diverse milk samples. A sample preparation procedure involving protein precipitation, extractant drying, and reconstitution was optimized for the effective extraction and quantification of all analytes. This streamlined procedure was evaluated by accuracy and precision analysis at five fortification levels, ranging from 0.01 to 0.25 µg/kg, equivalent to 10 to 250 ng/L in the final sample solution for LC-MS/MS analysis. Eighteen isotopes, serving as quantitative internal standards, were added to the sample before extraction to ensure accurate quantification by correcting variations in sample preparation, matrix effects, and instrument response. Calibration ranges varied among different analytes, spanning from 4 – 2500 ng/L. All analytes exhibited recovery values within 30 % of the nominal concentration across all fortification levels. Satisfactory method precision was demonstrated with %RSD values below 15 %. The established workflow was then applied to the analysis of additional milk samples collected from various grocery stores, providing a comprehensive profile of PFAS contamination across a diverse range of milk matrices.